Psychological and Social Predictors of Resilience among Indonesian University Students: The Roles of Hope, Social Support, and Sense of Humor - Alwis, Ulfy; Sanyata, Sigit; Sugiharta, Iip (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2026)
Resilience is an individual's ability to adapt to adversity, particularly among university students who face substantial academic and non-academic demands. Although previous studies have identified hope, social support, and sense of humor as factors associated with resilience, research integrating these variables simultaneously within a single predictive model remains limited, especially among Indonesian university students. Therefore, this study aimed to examine the effects of hope, social support, and sense of humor on student resilience. A quantitative approach with an ex post facto design was employed. The sample consisted of 379 students selected through a two-stage random sampling technique. Data were collected using standardized scales and analyzed using multiple linear regression. The results indicated that hope, social support, and sense of humor significantly predicted resilience (F = 119.295, p < .001, R² = .488). Individually, hope emerged as the strongest predictor, followed by sense of humor and social support. These findings support an integrative model of resilience that encompasses cognitive, social, and adaptive coping factors. The novelty of this study lies in the simultaneous examination of hope, social support, and sense of humor as predictors of resilience among Indonesian university students. The findings also provide practical implications for developing guidance and counseling services that promote hope, strengthen social support, and utilize humor as an adaptive coping strategy in higher education settings.